2021
DOI: 10.1186/s12889-021-11445-w
|View full text |Cite
|
Sign up to set email alerts
|

Developmental delay and its predictors among children under five years of age with uncomplicated severe acute malnutrition: a cross-sectional study in rural Pakistan

Abstract: Background In developing countries, malnutrition in children and developmental delays are two major challenges for public health. To achieve the vision of the Sustainable Development Goals from the broader perspective of child health, early identification of developmental delays and timely intervention are crucial. The aim of this study is to assess the prevalence of suspected developmental delay and their predictors in children under the age of 5 years with uncomplicated severe acute malnutrit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 26 publications
1
8
1
4
Order By: Relevance
“…A higher consumption rate of RUFs product would result in a faster and greater recovery rate in terms of weight gain among infants compared to CSB+. However, the weight gain obtained in the present study was higher than the one reported in previous studies for children receiving regular CSB+ (Thakwalakwa et al, 2010).…”
Section: Porridge Feeding In the Follow-up Periodcontrasting
confidence: 91%
See 1 more Smart Citation
“…A higher consumption rate of RUFs product would result in a faster and greater recovery rate in terms of weight gain among infants compared to CSB+. However, the weight gain obtained in the present study was higher than the one reported in previous studies for children receiving regular CSB+ (Thakwalakwa et al, 2010).…”
Section: Porridge Feeding In the Follow-up Periodcontrasting
confidence: 91%
“…It occurs when there is severe weight loss, possibly caused by inadequate energy and protein intake or chronic health conditions (Tut & Tsegaye, 2020 ; Dipasquale et al, 2020 ). Children with moderate acute malnutrition (MAM) have an increased risk of infections and mortality, higher chances of suffering the consequence of suboptimal adult work capacity, and an increased risk of disease in adulthood (Saleem et al, 2021 ; Cichon et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The variability of findings may be attributed to differences in sample size, socioeconomic status, nutritional status, health conditions and the methods implemented. For example, an extremely high magnitude (61.1%) of developmental delay was found among children with severe acute malnutrition in a study conducted elsewhere 21 and 50% of developmental delay was observed among children under five with chronic under-nutrition. 20 Moreover, higher prevalence of developmental delay was reported in underweight, wasted and stunted under-five children elsewhere.…”
Section: Discussionmentioning
confidence: 95%
“…Impaired growth and stunting are major public health issues associated with mortality and morbidity of children under 5 years of age 21 22. Approximately 56% of children globally suffer from stunting 23.…”
Section: Introductionmentioning
confidence: 99%